Minimizing water consumption for biofuel and bioproduct conversion from lignocellulosic biomass - Zhao, Jikai (Kansas State University, 2022)
Global demand for renewable biofuels and biochemicals has been promoting the development of biomass valorization technologies. However, the efforts have not led to its commercial realization. To unlock the recalcitrant biomass, pretreatment is an inevitably critical step. Unfortunately, excessive water washing of the pretreated biomass with wastewater discarding significantly causes water overconsumption and chemicals loss. The goal of this research was to minimize water consumption for biofuel and bioproduct conversion from biomass in an economically viable manner. The first chapter aimed to answer three prevalent questions: (i) why is excessive water washing needed after biomass pretreatment? (ii) is the higher solid loading used for pretreatment, hydrolysis, and fermentation better? (iii) why are most of the proposed economically viable biorefineries still not commercialized? Regarding the reduction in water consumption and enhancement of sugar and ethanol concentrations, physicochemical and biological detoxification, black liquor recycling, fed-batch model, strain genetic engineering, and ethanol (first and second generations) integration approaches were critically discussed in terms of strengths and weaknesses. Collectively, biomass-to-ethanol commercialization necessitates a comprehensive understanding of economic, environmental, and policy perspectives. Technoeconomic analysis as an essential valuation for potential commercialization from laboratory scale is recommended, and it should be relaying on accurate experimental data rather than an overrated empirical assessment. The second chapter evaluated the potential of acetic acid (HOAc)-sodium hydroxide (NaOH) integrated pretreatment of biomass to reduce water and chemicals consumption. Pretreatment effectiveness including morphology, crystallinity, and component recovery was elucidated. Results showed that HOAc and NaOH in the mixed filtrate were neutralized to achieve a pH of around 4.80 resulting in the alkali lignin precipitation. Lignin (46.01 and 48.38 g/kg-biomass for hemp and poplar, respectively) exhibiting comparable Fourier transform infrared spectroscopy (FTIR) characteristics with the commercial alkali lignin was recovered. Compared to sodium acetate buffer as a control, integrating HOAc and NaOH pretreated biomass and their mixed filtrate for enzymatic hydrolysis boosted total sugar concentration (hemp: 42.90 vs. 38.27 g/L; poplar: 43.18 vs. 38.76 g/L) without compromising glucose yield (hemp: 70.86 vs. 70.69%; poplar: 66.48 vs. 69.48 %) but improving xylose yield (hemp: 60.10 vs. 35.92%; poplar: 56.90 vs. 29.39 %). The third chapter revealed the effects of post-washing [one-volume water (I-VW) or double-volume water (II-VW)] on pretreated biomass and enzymatic hydrolysis. Compared to I-VW, II-VW increased 3.76-6.80% of glucan content in NaOH pretreated biomass, diminished lignin recondensation, and heightened cellulose-related FTIR peak intensities, crystallinity index, and lignin removal. The pH of the mixed filtrate was around 4.80, precipitating the NaOH soluble lignin partially. Although II-VW had lower lignin recoveries than I-VW, their FTIR characteristics were equivalent to the commercial alkali lignin. Enzymatic hydrolysis at solid loadings of 2.5-10% (w/v) demonstrated that I-VW and II-VW had marginal variations in sugar concentration and conversion efficiency, indicating that I-VW is sufficient for post-washing pretreated biomass. Glucose concentration exhibited a quadratic correlation with solid loading and hemp biomass reached the maximum glucose (43.88 g/L) and total sugar (57.08 g/L) concentrations with I-VW. The fourth chapter validated the potential of HOAc-NaOH integrated pretreatment for glucose, xylose, 5-hydroxymethylfurfural (HMF), furfural, and lignin production of four genotypes of industrial hemp biomass that were harvested from Haysville and Manhattan, KS. The integration process effectively rendered the pH of the integrated filtrate and slurry to approximately 4.80. The highest lignin recovery of 73.13 g/kg biomass was achieved by Rigel from Manhattan. FTIR spectrum showed that only lignin derived from Vega (Haysville) and Anka (Manhattan) was comparable to the commercial alkali lignin. Retaining monosaccharides (2.24-3.81 g/L) enhanced sugar concentrations (glucose: 40.40-45.71 g/L; xylose: 7.09-8.88 g/L) and conversion efficiencies (glucose: 71.19-77.71%; xylose: 45.42-52.03%). Besides, 0.79-1.25 g/L of HMF and 0.99-1.59 g/L of furfural coupling with 1.96-2.95% and 10.00-14.65% conversion efficiencies, respectively, were obtained in the final hydrolysate. The fifth chapter performed three pretreatment scenarios (I: H₂SO₄ pretreatment with NaOH neutralization; II: NaOH pretreatment with H₂SO₄ neutralization; and III: parallel H₂SO₄ and NaOH pretreatments following their integration) with enzymatic hydrolysis for glucose, xylose, HMF, furfural, bioethanol production at high solid (15 and 25%, w/v) loading without solid-liquid separation and further detoxification. With an initial solid loading of 25% (w/v), scenario I reached the highest furfural (4.94 g/L) and HMF (2.82 g/L) concentrations, scenario II achieved the highest glucose (73.25%) and xylose (77.49%) yields, while scenario III displayed the highest sugar concentration (74.53 g/L). Only the hydrolysate from NaOH pretreatment and enzymatic hydrolysis with 10% initial solid loading can be efficiently fermented to ethanol (17.92 g/L) by the traditional yeast. In summary, integrating acid and alkali pretreatment of biomass has great potential to reduce water consumption for multi-stream biofuel and bioproduct production. There is a lot of room for further research on upgrading sugar and lignin to high-value chemicals.
Keywords: Biomass pretreatment; Biofuel production; Water consumption; Ethanol fermentation